Third Five-Year Plan A Draft Outline Government of Orissa - Planning Commission (Planning Commission, 1960)
It is now a decade since Orissa along with other States began to draw up Plans for the Social and Economic development of its people. The First Five-Year Plan of the State like that of the rest of the country was largely designed to repair the damages caused by war and was in the main confined to continuing the programmes taken up during the post-war period. Nevertheless it represented the first step in planned development and prepared the ground for a larger effort in the Second Five-Year Plan. The most noteworthy programmes undertaken during this period were the Hirakud Dam Project and the introduction of the National Extension Service. The Second Plan was conceived on a somewhat bigger scale. The above two major programmes were continued.
Planning and Co-ordination (Planning) Department